The influence of institutional environment on venture capital development in emerging economies: The example of Nigeria1. (13th January 2019) - Ekanem, Ignatius; Owen, Robyn; Cardoso, Antonio
Abstract: Venture capital (VC) can be nurtured in the right environment, within an emerging economy, to be attractive to private VC investment development. Venture capitalists require stable institutional frameworks, regulations, and tax regimes alongside clear exit strategies. Informal institution such as networking is important for VC development. Governments of emerging economies need to stimulate entrepreneurial awareness of equity finance through training and promotion to facilitate investment readiness.